Assessment of prevalence, nature, and factors associated with substance abuse among medical undergraduate students in Northern India - Suneel Kumar; Himani Deswal; Jyoti Kaushal; Jyoti Sharma; Monika Verma; Niti Mittal (Asian Journal of Medical Sciences, 2025)
Background: In recent years, drug abuse among the student population has increased to an alarming rate in India and that too among medical students. Substance abuse among medical students has important implications for their personal health, training, and clinical practice. Aims and Objectives: To plan effective interventions, it is essential to have information on the extent, type, and factors associated with substance abuse among medical students. Hence this study was undertaken to find the prevalence and pattern of substance abuse. Materials and Methods: A cross-sectional study was conducted among undergraduate medical college students of all professional years. Students were assessed for their pattern and prevalence of substance abuse with the help of a structured self-administered questionnaire entitled “Pattern of substance abuse among medical students” as a tool for data collection. The questionnaire had three domains viz. demographic characteristics, short Michigan alcohol screening test, and Fagerstrom test for assessment of level of nicotine dependence. The World Health Organization-Alcohol, Smoking, and Substance Involvement Screening Test Scale was also used to increase the validity of results. Results: Alcohol and Nicotine were the most commonly abused substances among medical students. The trend of abusing a substance increases as per increase in the ladder of professionalism. The majority of students initiated abuse because of peer pressure and mental stress during their academic life. The problem was more among hostellers. Most of the students continued the abuse because of the feeling of enjoyment and to increase their performance in the exams. Conclusion: Awareness creation and academic counseling camps along with stress interventions are recommended and needed to curb drug abuse among medical students.